Women warriors as personifications of Armenia in Classical Antiquity - Vasilyan, Viktorya (ARAMAZD: Armenian Journal of Near Eastern Studies, 2017)
The problem of personification is one of the topical issues in art history and archaeology. Some of the most interesting studies on classical art in the recent decades have focused on personifications and allegories of different nations and ethnic groups. Personifications were popular in the art of ancient Greece and Rome, and later, they were used in the early Eastern Christian art and in the monuments of those countries of the Hellenistic world where traditions of ancient culture continued to live.